Urban or Rural: Where are people happier and why? - Berticelli de Freitas, Abilio Henrique (Papeles de Europa, 2021)
Using data from a worldwide sample, we investigate how happy people look like and if these “happiness characteristics” are more present in big urban towns or in small rural villages. We found evidence that (i) people seem to be slightly happier in rural settlements, (ii) happier people have some particular characteristics (e.g., higher levels of trust in others and being more interested in politics) and (iii) these positive attitudes are slightly more present in rural contexts. Then, we discuss some conceivable explanations to what we have seen.